Cannabinoid Modulation of Emotion, Memory, and Motivation 2015
DOI: 10.1007/978-1-4939-2294-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Modulation of Emotional and Non-Emotional Memory Processes After Stress

Abstract: The endocannabinoid system (ECS) is involved in regulating the stress response and subsequent changes in neuroendocrine function and emotional behavior. It is also a critical neuromodulatory system that affects learning and memory. Generally systemically administered cannabinoid agonists have an impairing effect on memory processes although enhancing effects are also reported.Stress is a potent modulator of brain function and cognition that has differential effects on memory function depending on a number of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…It has also been found that the interaction between the ECS and microbiome affects brain and gut activity in a bidirectional manner [20][21][22]. The ECS plays a role in modulating both emotional and non-emotional behavior [23][24][25][26]. Signals originating from the ECS are known to influence the hypothalamic-pituitary-adrenocortical (HPA) axis, which is the mammals' primary stress response system [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the interaction between the ECS and microbiome affects brain and gut activity in a bidirectional manner [20][21][22]. The ECS plays a role in modulating both emotional and non-emotional behavior [23][24][25][26]. Signals originating from the ECS are known to influence the hypothalamic-pituitary-adrenocortical (HPA) axis, which is the mammals' primary stress response system [27][28][29].…”
Section: Introductionmentioning
confidence: 99%